2016
DOI: 10.1021/jacs.6b08933
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Triggered Chemical Rescue of Intracellular Proteins via Genetically Encoded Allene-Caged Tyrosine

Abstract: Chemical de-caging has emerged as an attractive strategy for gain-of-function study of proteins via small-molecule reagents. The previously reported chemical de-caging reactions have been largely centered on liberating the side chain of lysine on a given protein. Herein, we developed an allene-based caging moiety and the corresponding palladium de-caging reagents for chemical rescue of tyrosine (Tyr) activity on intracellular proteins. This bioorthogonal de-caging pair has been successfully applied to unmask e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
123
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 42 publications
1
123
0
2
Order By: Relevance
“…Early mechanistic studies have identified Ubal as the first Ub activity based probe,w hich forms hemithioacetals with the active site Cys of DUBs in presence of complex biological molecules. [29][30][31][32] Inspired by this work, Thzc leavage was achieved in cell lysates for the labeling of as ide-chain aldehyde. We have recently demonstrated the cleavage of peptides,bearing backbone Thz, using [PdCl(allyl)] 2 , [25,28] which is known to be compatible with reactions in live cells because of its reported low toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Early mechanistic studies have identified Ubal as the first Ub activity based probe,w hich forms hemithioacetals with the active site Cys of DUBs in presence of complex biological molecules. [29][30][31][32] Inspired by this work, Thzc leavage was achieved in cell lysates for the labeling of as ide-chain aldehyde. We have recently demonstrated the cleavage of peptides,bearing backbone Thz, using [PdCl(allyl)] 2 , [25,28] which is known to be compatible with reactions in live cells because of its reported low toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…The UAA mutagenesis approach requires minimal engineering of the protein of interest; when the proper orthogonal translational machinery is provided, UAAs are incorporated simply by mutating the codon at the desired position to the amber stop codon . UAAs allow investigators to site‐specifically insert new chemical functionalities into proteins, thereby enabling small‐molecule control in live biological systems . For example, palladium complexes can trigger protein function using propargylated or allylated lysine and allenylated tyrosine .…”
Section: Introductionmentioning
confidence: 99%
“…UAAs allow investigators to site‐specifically insert new chemical functionalities into proteins, thereby enabling small‐molecule control in live biological systems . For example, palladium complexes can trigger protein function using propargylated or allylated lysine and allenylated tyrosine . Additionally, tetrazine‐mediated triggering of UAAs masked with trans ‐cyclooctene (TCO) moieties provides another clever approach to conditional control over protein function .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Specifically,t he discovery of palladium-mediated carbon-carbon bond formation and carbon-oxygen bond cleavage,which revolutionized organic synthesis,isnow being successfully applied to protein modification. [24] Theunique catalytic properties of palladium in C À Cbond formation and C À Ob ond cleavage is due to the presence of as quare-planar geometry of palladium(II) complexes (d 8 ), with extra coordination sites at the axial positions which can accommodate various ligands for different chemistries.Moreover the unique ground-state structure of palladium (4d 10 5s 0 ), Pd 0 ,w here the filled dorbital can combine with the empty frontier sorbitals,a lso provides important properties to palladium catalysis. [23] Furthermore,less toxic palladium reagents are being used to modulate the activity of enzymes for ag ain of function by decaging catalytic residues.…”
Section: Introductionmentioning
confidence: 99%